Pharmaceutical Poisoning Exposure and Outcome Analysis in Children Admitted to the Pediatric Emergency Department - Yan-Ren Lin; Tzu-Hsuan Liu; Tzu-An Liu; Yu-Jun Chang; Chu-Chung Chou; Han-Ping Wu (Pediatrics and Neonatology)
Pharmaceuticals involved in childhood poisoning vary, and treatment of poison exposure can be a challenge for primary physicians when children are unconscious or histories are lacking. Knowledge of the clinical manifestations and prognosis of poisoning will help primary physicians perform appropriate clinical assessments. In this study, we aim to report on patient characteristics, outcomes, and clinical features of pediatric poisoning in the emergency department. Methods: We retrospectively evaluated the medical records of 87 children younger than 18 years of age and presented to the emergency department with pharmaceutical poisoning (2001–2008). The detailed categories of pharmaceutical were reported, and their associations with patient outcomes were analyzed. Furthermore, children were divided into two groups, based on the reasons for poison exposure (accidental or intentional poisoning). Clinical features and outcomes between accidental or intentional poisoning were analyzed, and the cut-off age for high risk of intentional poisoning was also calculated. Results: Age groups of adolescents (48.3%) and preschool age (32.2%) children were the major representation. Neurologic system agents (48.3%) and analgesics (18.4%) were the most common causes of poisoning. Among the two major agents above, anxiolytic/hypnotic drugs (lorazepam) and acetaminophen were the most frequent causes. Of all children, 70.1% had duration of major symptoms for ≤1 day, and intentional poisoning caused significantly longer duration of hospital stay than accidental poisoning did (p=0.008). Moreover, female gender (p<0.001), older age (p<0.001), and analgesics (p=0.008) were more predominantly associated with intentional poisoning in children, and the cut-off age for high risk of intentional poisoning was over 10.5 years. Conclusion: Neurologic system agents and analgesics were responsible for the majority of cases. Intentional poisoning caused longer hospital length of stay than accidental poisoning, and the factors associated with intentional poisoning were older age, female, and neurologic system agents.